Cardiovascular risk factors in semi-urban communities in southwest Nigeria: Patterns and prevalence - Rotimi Oluyombo; Michael A. Olamoyegun; Oluwasegun Olaifa; Sandra O. Iwuala; Oluwole A. Babatunde (Springer, 2019)
Introduction: Over 80% of cardiovascular deaths take place in low- and middle-income countries; most of these deaths are due to modifiable risk factors. The study aimed at estimating the prevalence and pattern of major cardiovascular risk factors in both men and women older than 18 years. Methods: This is a cross-sectional study of cardiovascular risk factors among semi-urban dwellers in Ekiti State, south-western, Nigeria. 750 participants were drawn from 10 communities. The instrument used was the standard WHO STEPS (II) questionnaire, while blood samples were obtained for analysis. Results: There were 750 participants with 529 (70.53%) females. The mean age of participants was 61.7 ± 18.50 years and participants' ⩾65 years comprised 38.3%. There were 0.8%, 24.9% and 12.4%, who at the time of this study smoked cigarettes, consumed alcohol, and ate a high salt diet, respectively. The prevalence of hypertension, diabetes, generalized and abdominal obesity was 47.2%, 6.8%, 8.5% and 32.0%, respectively, with only 48.9% receiving hypertension treatment. Elevated total cholesterol, LDL-cholesterol, and low HDL was seen in 4.4%, 16.7% and 56.3% respectively. Conclusion: High prevalence of cardiovascular risk factors call for an urgent need for more public health attention and reinforcement of primary preventive strategies to curb its menace.